Spontaneously Fluctuating Motor Cortex Excitability in Alternating Hemiplegia of Childhood: A Transcranial Magnetic Stimulation Study - Stern, William M. (PLoS One, 2016)
BACKGROUND: Alternating hemiplegia of childhood is a very rare and serious neurodevelopmental syndrome; its genetic basis has recently been established. Its characteristic features include typically-unprovoked episodes of hemiplegia and other transient or more persistent neurological abnormalities. METHODS: We used transcranial magnetic stimulation to assess the effect of the condition on motor cortex neurophysiology both during and between attacks of hemiplegia. Nine people with alternating hemiplegia of childhood were recruited; eight were successfully tested using transcranial magnetic stimulation to study motor cortex excitability, using single and paired pulse paradigms. For comparison, data from ten people with epilepsy but not alternating hemiplegia, and ten healthy controls, were used. RESULTS: One person with alternating hemiplegia tested during the onset of a hemiplegic attack showed progressively diminishing motor cortex excitability until no response could be evoked; a second person tested during a prolonged bilateral hemiplegic attack showed unusually low excitability. Three people tested between attacks showed asymptomatic variation in cortical excitability, not seen in controls. Paired pulse paradigms, which probe intracortical inhibitory and excitatory circuits, gave results similar to controls. CONCLUSIONS: We report symptomatic and asymptomatic fluctuations in motor cortex excitability in people with alternating hemiplegia of childhood, not seen in controls. We propose that such fluctuations underlie hemiplegic attacks, and speculate that the asymptomatic fluctuation we detected may be useful as a biomarker for disease activity.